Preconception and perinatal predictors of offspring attachment disorganization: Advancing the replicated evidence. (February 2021) - McIntosh, Jennifer E.; Schnabel, Alexandra; Youssef, George J.; Olsson, Craig A.
Abstract: Attachment disorganization in early childhood is an influential yet modifiable risk factor for later mental health problems. Beyond established transmission through parents' unresolved attachment representations and caregiving sensitivity, little replicated evidence exists for wider determinants of offspring attachment disorganization. This study examined the replicated evidence for psychosocial risk factors in the preconception, prenatal, and postnatal periods. We identified all relevant longitudinal studies, and examined all risk relationships for which evidence existed in two or more cohorts (48 effects, 17 studies, N = 6, 099). Study-specific and pooled risk associations were estimated and a range of moderators evaluated. Mothers' low socioeconomic status (r = .28, k = 2), perinatal loss of a child (r = .26, k = 2), caregiving intrusiveness (r = .31, k = 2), and infant male sex (r = .26, k = 4) predicted offspring attachment disorganization. Maternal sensitivity (r = –.25, k = 6) and higher metacognition during pregnancy (r = –.23, k = 3) predicted lower risk of offspring attachment disorganization. Findings suggest the origins of offspring disorganized attachment include but extend beyond maternal unresolved attachment representations and caregiving. We discuss implications for theory and for identification of modifiable risk pathways in the perinatal window.